A comparison of medication profiles held by general practitioners and those documented during Home Medication Reviews. (4th August 2018) - Carson, Sue; Kairuz, Therese
Abstract: Background: The Home Medication Review (HMR) is a specialised medication management service designed to maximise medication safety and quality use of medicines. Aim: To identify the type and number of discrepancies between information elicited during an HMR and information documented in general practitioner (GP) referral letters, and to determine the potential risk and clinical impact of discrepancies. Method: GP referral letters and HMR medication profiles of 60 consenting HMR recipients were compared to identify discrepancies. Discrepancies were grouped according to five types. For each discrepancy the potential clinical risk was determined relative to individual subjects and classified as minimal, moderate or severe. A case study approach was used to calculate hypothetical economic implications if discrepancies had not been detected. Results: There were 833 medications in the dataset and subjects took between three and 24 medications (average 10.4 per subject). Of the 247 discrepancies the greatest number were related to dose (24.6%; n = 61), followed by not taking prescribed medicines (23.1%; n = 57), taking complementary therapies (20.6%; n = 51) and prescription medicines which were not documented in the referral letter (17.4%; n = 43) and over‐the‐counter (OTC) medicines (14.2%; n = 35). Just over one‐fifth of discrepancies (55/247) had potential to cause serious clinical consequences, with dose discrepancies of prescribed medications associated with over one‐third (36.4%, 20/55). Conclusion: Altered doses, patients not taking prescribed medicines, or taking complementary and alternative medicines, other prescription medicines or OTC products were common discrepancies. Serious risks were associated with taking (other) prescription medicines which were not included in the referral letter. Abstract :